INTEGRATION OF ISLAMIC EDUCATION VALUES IN THE FORMATION OF GENERATION Z CHARACTER IN THE DIGITAL ERA - Samhudi, Samhudi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
The development of the digital era presents new challenges in the character building of Generation Z, who were born and grew up in a technological environment. In this case, Islamic education is crucial in shaping their morals and ethics to remain aligned with Islamic teachings. This study aims to examine the integration strategy of Islamic education values in the character building of Generation Z in the digital era, with a research focus on class XI students of SMAN 1 Nisam who have an average age of 16 to 17 years old. This research uses a qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the strategies used by the teacher of SMAN 1 Nisam to integrate the Islamic Education values in character building are applied through morals-based learning, religious activities, digital media utilization, and Islamic attitude habituation. The integrated Islamic Education values include the values of aqidah, morals, and social responsibility, which aim to shape students' personalities so that they can face digital challenges wisely.